Penerimaan konsep kafe sawah Yogyakarta sebagai pemberdayaan ekonomi berbasis lingkungan ditinjau melalui pendekatan TAM dan UTAUT - Wahyudi, Eko Juni; Isroani, Farida (Universitas Halu Oleo, 2023)
The acceptance of local potentials and resources for the management of land with the concept of rice fields to be used as shops (paddy cafes). Several changes also accompanied, including the acceptance point of view by the community in which the concept of a rice field cafe is considered a driving force and an impetus for the community's economy. Of course, this is an interesting urgency for presenting scientific research that aims to find out which variables affect the acceptance of innovation in the form of a rice field cafe concept involving 51 respondents, and then uses the integration of two approaches, namely TAM and UTAUT. For UTAUT, a new variable was added, which was Brand and Service Trust. Then, all of these variables were formed into a conceptual model and processed with the SmartPLS 3.0 software. The obtained results indicate the acceptance of 7 out of 8 hypotheses. This shows the positive influence of the respondents on the acceptance of the visit and their willingness to be exposed to the concept of a rice field cafe. The final result of this research is that the respondents of this research have felt the acceptance of the development of the economic potential resulting from the rice field cafe concept.